Reflections on the "General Idea of Revolution" at the Beginnig of the 21st Century - Laval, Christian (Analysis. Journal of Philosophical Research, 2018)
II Miguel Servet Lecture. Christian Laval. Universidad de Zaragoza, November 8, 2017.